Perluasan Unsur Obyektif Tindak Pidana Pemilihan dalam Pasal 188 jo Pasal 71 Undang-Undang Pemilihan Gubernur, Bupati, dan Waliko - La Ode Muhamad Sulihin (Indonesia Law Reform Journal, 2021)
The principle of legality is a very fundamental principle in criminal law, which applies both in material criminal law and in formal criminal law. In the context of material criminal law and formal criminal law, the formulation of the offense occupies a very important place because it is a concrete application of the legality principle itself and shows what must be proven according to law. This research is a normative legal research with the type of legal research for in-concrito cases. The purpose of this study is to examine a normative postulate that can or cannot be applied to a concrete case. In the enforcement of criminal law against criminal acts of election of Governors, Regents and Mayors as stated in the decisions of the Andoolo District Court Number 1/Pid/S/2020/PN Adl and Number 2/Pid/S/2020/PN Adl, there are deviations from the basic principles legality and principles of interpretation in criminal law, namely by expanding the objective element or the meaning of actions as regulated in Article 71 of the Law on the Election of Governors, Regents and Mayors. Therefore, in general, this paper describes the form of expansion of the objective elements of criminal acts of election of Governors, Regents and Mayors as regulated in Article 188 in conjunction with Article 71 of the Law on the Election of Governors, Regents and Mayors in the implementation of the Regent election in Konawe Selatan Regency in 2020. Expansion of objective elements what is meant is declaring the act of taking an action or decision in favor of one of the pairs of candidates committed outside the campaign period as a criminal act. Abstrak Asas legalitas merupakan asas yang sangat fundamental dalam hukum pidana, yang berlaku baik dalam hukum pidana materiil maupun dalam hukum pidana formil. Dalam konteks hukum pidana materiil dan hukum pidana formil, rumusan delik menduduki tempat yang sangat penting karena merupakan penerapan konkret dari asas legalitas itu sendiri serta menunjukan apa yang harus dibuktikan menurut hukum. Penelitian ini adalah penelitian hukum normatif dengan jenis penelitian hukum untuk perkara in-concrito. Tujuan penelitian ini adalah untuk menguji sebuah postulat normatif dapat atau tidak dapat diterapkan untuk sebuah perkara konkret. Dalam penegakan hukum pidana terhadap tindak pidana pemilihan Gubernur, Bupati dan Walikota yang tertuang dalam putusan PN Andoolo Nomor 1/Pid/S/2020/PN Adl dan Nomor 2/Pid/S/2020/PN Adl, terdapat penyimpangan terhadap prinsip-prinsip asas legalitas maupun prinsip-prinsip penafsiran dalam hukum pidana yaitu dengan memperluas unsur obyektif atau makna perbuatan yang diatur dalam Pasal 71 UU Pemilihan Gubernur, Bupati dan Walikota. Oleh karena itu, secara umum tulisan ini menguraikan bentuk perluasan unsur obyektif tindak pidana pemilihan Gubernur, Bupati dan Walikota yang diatur dalam Pasal 188 jo Pasal 71 UU Pemilihan Gubernur, Bupati dan Walikota pada pelaksanaan pemilihan Bupati di Kabupaten Konawe Selatan tahun 2020. Perluasan unsur obyektif yang dimaksud adalah menyatakan perbuatan melakukan tindakan atau keputusan menguntungkan salah satu pasangan calon yang dilakukan diluar masa kampanye sebagai tindak pidana.